2004
DOI: 10.1111/j.1365-2125.2004.02145.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oral fumarates in healthy subjects

Abstract: AimsTo characterize the pharmacokinetics of fumarates in healthy subjects. MethodsTen subjects received a single fumarate tablet (containing 120 mg of dimethylfumarate and 95 mg of calcium-monoethylfumarate) in the fasted state and after a standardized breakfast in randomized order. Prior to and at fixed intervals after the dose, blood samples were drawn and the concentrations of monomethylfumarate, the biologically active metabolite, as well as dimethylfumarate and fumaric acid were measured using high-perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 16 publications
4
103
0
6
Order By: Relevance
“…However, DMF does not seem to be the bioactive ingredient because it is not detected in patients' blood for a sufficient length of time to be exerting an action on its own (Litjens et al, 2004a). Furthermore, according to previous clinical and experimental studies, most of the DMF is hydrolyzed to MMF, which, in turn, is thought to act as an antipsoriatic agent (Rostami Yazdi and Mrowietz, 2008;Rostami-Yazdi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, DMF does not seem to be the bioactive ingredient because it is not detected in patients' blood for a sufficient length of time to be exerting an action on its own (Litjens et al, 2004a). Furthermore, according to previous clinical and experimental studies, most of the DMF is hydrolyzed to MMF, which, in turn, is thought to act as an antipsoriatic agent (Rostami Yazdi and Mrowietz, 2008;Rostami-Yazdi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…MMF treatment was associated with significant increases in the expression of Nrf2-responsive antioxidant genes and a suppression of inflammatory responses as evidenced by increased expression of NAD(P)H quinone dehydrogenase 1, thioredoxin reductase 1 and hemeoxygenase-1 along with decrease in interlukin-1β, chemokine (C-C motif) ligand expressions [2,7,12]. Collectively, these molecular improvements interpreted to improve retinal function as evidenced by electroretinogram recordings performed on live mice.…”
Section: Editorialmentioning
confidence: 89%
“…Immediately after oral intake, DMF is acted upon by intestinal esterases to form Monomethyl Fumarate (MMF); hence, MMF is the primary bioactive ingredient [6]. Following DMF ingestion, circulating MMF concentrations peak between 2-2.5 hrs and the half-life of the metabolite is around 12 hrs [7]. Recent studies have reported the use and potential efficacy of MMF in the treatment of various diseases other than those named above.…”
Section: Editorialmentioning
confidence: 99%
“…33 Therefore patients taking DMF should have a complete blood count (CBC) before starting treatment to measure lymphocyte count and an annual follow up CBC investigation.…”
Section: Adverse Effectsmentioning
confidence: 99%